STUDI ETNOBOTANI TUMBUHAN OBAT MASYARAKAT DI DESA PASTINA KECAMATAN SANANA KABUPATEN KEPULAUAN SULA - Khardy Soamole; Euis F.S. Pangemanan; Wawan Nurmawan (Universitas Sam Ratulangi, 2018)
ABSTRACTTraditional medicine is part of a cultural system of people whose benafits are very large in the development of public health. As a first step it is very helpful to know a plant with medical poroperties is from the knowledge of the community for generations.this study aims to determine the type and utilization of traditionl community medicinal plants in Pastina village Sanana Distirct Sula Islands Regency. This research was carried out in March – April 2017. The data was collected by interviewing Batra using questionnaires and the data were analyzed by descriptife analysis and presented in the from of tables and figure. The results of this study found 53 types of plants and 39 families that were utilized as traditional medicine. The most numerous families are Araceae and Fabaceae. Keywords : Traditional medicine, medicinal plants, Pasina village.